2022
DOI: 10.1111/his.14713
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in colorectal carcinoma: a review of its significance as a predictive and prognostic biomarker

Abstract: Colorectal carcinoma is a leading cause of cancer‐related death worldwide. There is significant prognostic heterogeneity in stages II and III tumours, necessitating the development of new biomarkers to more clearly identify patients at risk of disease progression. Recently, the tumour immune environment, particularly the type and quantity of T lymphocytes, has been shown to be a useful biomarker in predicting prognosis for patients with colorectal carcinoma. In this review, the significance of the immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…The diagnostic criteria following the renaming of MAFLD highlight the important role of metabolic dysfunctions in the development of fatty liver disease and may be more appropriate for identifying patients with fatty liver disease at high risk of disease progression [ 13 ]. CRC is a malignant tumor with a high mortality rate, and CRC incidence is increasing annually; therefore, early prevention of CRC is particularly important [ 23 ]. A large number of studies and clinical practices have shown that colorectal cancer screening and early diagnosis and treatment can effectively reduce the incidence and mortality of colorectal cancer [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criteria following the renaming of MAFLD highlight the important role of metabolic dysfunctions in the development of fatty liver disease and may be more appropriate for identifying patients with fatty liver disease at high risk of disease progression [ 13 ]. CRC is a malignant tumor with a high mortality rate, and CRC incidence is increasing annually; therefore, early prevention of CRC is particularly important [ 23 ]. A large number of studies and clinical practices have shown that colorectal cancer screening and early diagnosis and treatment can effectively reduce the incidence and mortality of colorectal cancer [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses and research studies reported a favorable prognosis with higher immune infiltration at the invasive front of tumors [ 56 , 57 ] in contrast to the non-invasive front [ 58 , 59 ]. In our study, we selected the tumor center area for evaluation because the TAMs in the invasive front showed substantial bias for the examiner in the preliminary experiment (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Most colorectal carcinoma (CRC) cases feature uncontrolled growth of epithelial cells of the colorectal mucosa [ 1 ]. During CRC development, tumor immunity is mounted to restrain CRC expansion and invasion [ 2 ]. Natural killer (NK) cells efficiently kill tumor cells by secreting cytotoxic granules and expressing death ligands [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%